Pengaruh Faktor-Faktor Kolusi Terhadap Kecurangan Laporan Keuangan - Tio Daresta; Elly Suryani (SEIKO : Journal of Management & Business, 2022)
Abstract Fraud is an act carried out intentionally by an individual or a certain group to obtain a personal or collective advantage. Fraudulent financial reporting can be done by manipulating and falsifying important information in the financial statements. Collusion is the existence of an illegal contract or secret cooperation that is contrary to applicable law but seems reasonable with the aim of gaining mutual benefit. This study aims to determine the effect of collusion factors including political connections, related party transactions and state owned enterprises on financial statement fraud. Manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2020 constitute the population in this study of 193 companies. The resulting sample is 57 companies using purposive sampling. The analytical method used is logistic regression using SPSS 26 software. The results of the tests that have been carried out show that the independent variables of political connections, related party transactions and state owned enterprises have a significant effect on fraudulent financial statements simultaneously. While partially related party transactions have a positive effect on the detection of fraudulent financial statements. Compared to political connections and state owned enterprises, it has no significant effect in detecting fraudulent financial statements. Keywords: fraudulent financial reporting, political connections, related party transaction and state-owned enterprises.